Easier and more explanatory indices by integrating leukocyte lymphocyte ratio (LLR) and prognostic nutritional index (PNI) to IPS systems in cases with classical Hodgkin lymphoma. (August 2021) - Paydas, Semra; Lacin, Sahin; Dogan, Mutlu; Barista, Ibrahim; Yildiz, Birol; Seydaoglu, Gulsah; Karadurmus, Nuri; Civriz, Sinem; Kaplan, Muhammed Ali; Yagci, Munci; Dincyurek, Huseyin Derya; Ercolak, Vehbi
Highlights: In this study, leukocyte lymphocyte ratio (LLR) and prognostic nutritional index (PNI) were integrated to IPS-3 system and 2 scores named as IPS-4 were created; IPS-4 with PNI and IPS-4 with LLR. There was an acceptable agreement between IPS-3 and IPS-7 groups and IPS-4. These findings need to be confirmed with other studies and the incorporation of pre-therapy PET/CT metabolic parameters including total lesion glycolysis and total metabolic tumor volume to IPS-4 scores may be more informative and may help to predict response to first-line therapy. Abstract: The aim of this study is to determine the power of he international prognostic scoring systems (IPS-7 and IPS-3) and to obtain indices by integrating leukocyte lymphocyte ratio (LLR) and prognostic nutritional index (PNI) factors as prognostic indicators in cases with classical Hodgkin lymphoma (cHL). 1012 patients with cHL were evaluated with 2 different IPS-4 scores with four parameters: stage, age, hemoglobin level, and either LLR or PNI. Statistical package SPSS v 22.0 was used. Two different Cox regression models were obtained for OS and PFS. Model 1 showed LLR ≥ 5, 8 as the highest risk for OS and anemia as the highest risk for PFS. Model 2 showed PNI ≤ 45, 2 as the highest risk for OS and anemia as the highest risk for PFS. IPS-4 scores obtained by integrating either LLR or PNI to IPS-3 integration of a biologic parameter either LLR or PNI need to be determined with clinical risk scoring parameters.